Kinetic and Equilibrium Studies on the Biosorption of Cl Reactive Orange 16 Dye by Immobilized Scenedesmus quadricauda - TAN, SEMA; ERGENE, AYSUN; ADA, KEZBAN; KATIRCIOGLU, HIKMET (Asian Journal of Chemistry, 2010)
The biosorption of commonly used reactive dye, reactive orange 16 (RO 16), from aqueous solutions by live (ILSq) and heat inactivated Scenedesmus quadricauda (IHISq) immobilized Scenedesmus quadricauda was studied in a batch system with respect to pH, temperature and biosorption time. The ILSq and IHISq exhibited the highest dye uptake capacity at 30 °C, the initial pH value of 2.0 and the initial dye concentration of 300 mg L-1. At 300 mg L-1 initial dye concentration in the batch system the adsorption capacity was determined as 88.4 mg g-1 of dye biosorption for IHISq in 0.5 h. The adsorption capacity of ILSq was observed as 71.2 mg g-1 in 0.5 h and 76.4 mg g-1 and 82.8 mg g-1 of dye biosorption within 1 and 3 h, respectively. The equilibrium concentration and the adsorption capacity at equilibrium were determined using four different sorption models i.e., Langmuir, Temkin, Flory-Huggins and Freundlich isotherm.